THE EFFECT OF HORMONE REPLACEMENT THERAPY ON POSTMENOPAUSAL WOMEN - Melichaříková, Zuzana; Reslerová, Ludmila (Profese Online, 2009)
Aim: The authors' aim was to find out attitude of women to the solution of complications that are connected with the estrogen deficit, their interest in the hormone replacement therapy (HRT)and their knowledge of the risks related to undergoing the HRT.Methods: Research investigation was based on anonymous questionnaires of women in climacterium.Results: Acquired data are interpreted in tables and confronted in discussion.Conclusions: The purpose of investigation is positive attitude of women to HRT that is used in connection with severe hot flashes and sleep disorders. The women indicate breast cancer as the main risk relating to taking of HRT.
Keywords: climacterium; HRT; estrogen; contraindications; breast cancer; trombembolic disease